Physicochemical, Pre-Clinical, and Biological Evaluation of Viscosity Optimized Sodium Iodide-Incorporated Paste - Soo-Jin Chang; Yu-Jin Kim; Huong Thu Vu; Ji-Myung Choi; Jeong-Hui Park; Seong-Jin Shin; Khandmaa Dashnyam; Jonathan C. Knowles; Hae-Hyoung Lee; Soo-Kyung Jun; Mi-Ran Han; Joon-Haeng Lee; et al. (MDPI AG, 2023)
This study aimed to investigate the impact of different viscosities of silicone oil on the physicochemical, pre-clinical usability, and biological properties of a sodium iodide paste. Six different paste groups were created by mixing therapeutic molecules, sodium iodide (D30) and iodoform (I30), with calcium hydroxide and one of the three different viscosities of silicone oil (high (H), medium (M), and low (L)). The study evaluated the performance of these groups, including I30H, I30M, I30L, D30H, D30M, and D30L, using multiple parameters such as flow, film thickness, pH, viscosity, and injectability, with statistical analysis (p < 0.05). Remarkably, the D30L group demonstrated superior outcomes compared to the conventional iodoform counterpart, including a significant reduction in osteoclast formation, as examined through TRAP, c-FOS, NFATc1, and Cathepsin K (p < 0.05). Additionally, mRNA sequencing showed that the I30L group exhibited increased expression of inflammatory genes with upregulated cytokines compared to the D30L group. These findings suggest that the optimized viscosity of the sodium iodide paste (D30L) may lead to clinically favorable outcomes, such as slower root resorption, when used in primary teeth. Overall, the results of this study suggest that the D30L group shows the most satisfactory outcomes, which may be a promising root-filling material that could replace conventional iodoform-based pastes.